Peran Metode Failure Mode and Effect Analysis (FMEA) terhadap Mutu Pelayanan Rumah Sakit: Systematik Review - Anisa Sri Utami; Rahmi Fahmy; Zifriyanthi Minanda Putri (Universitas Batanghari Jambi, 2020)
Incidence of medication errors, nosocomial infections, falling patients, pressure sores (pressure sores) is often found in hospitals. This incident can be prevented by identifying the risk and finding the root of the problem using Failure mode and effect analysis (FMEA). This study aims to describe the effectiveness of the FMEA method on the quality of hospital services using a systematic review method. This research starts from searching for data using five databases with the keywords